Transforming agriculture in Africa & Asia: What are the policy priorities? - Laborde Debucquet, David; Lallemant, Tess; McDougal, Kieran; Smaller, Carin; Traoré, Fousseini (International Institute for Sustainable Development, 2018)
This report is the first attempt to map the agricultural transformation path of 117 countries over a 45-year period using an analytical framework with a global cluster analysis. The analytical framework is rooted in Timmer’s (1988) agricultural transformation framework and assesses the level of agricultural transformation by using data on the prevalence of undernourishment and the share of agricultural employment. Six non-linear phases of agricultural transformation are identified: (1) Industrialized economies; (2) agricultural integrated into the macro economy; (3) agriculture as a contributor to growth; (4) moving labour out of agriculture; (5) getting agriculture moving; and (6) subsistence agriculture.